QARAQALPAQ PROZASÍNDA DETEKTIV GÚRRIŃLERDIŃ TUTQAN ORNÍ (J.Óteniyazovtıń detektiv gúrrińleri mısalında) - Allamuratova, Z.M. (ILIM hám JÁMIYET, 2023)
The article discusses the use of detective forms in the stories of J. Uteniyazov. The essence of detective stories in Karakalpak literature is studied in detail and expressed with examples.